Monte Carlo Simulations of the effects of warm pre-stress on the scatter in fracture toughness. (January 2015) - Van Gelderen, D.G.A.; Rosahl, K.; Booker, J.D.; Smith, D.J.
Highlights: Reformulated Chell model is used with MCS to predict WPS distributions. Computationally efficient algorithm solves WPS equations automatically. Chell model provides conservative predictions compared to experimental results. Sample size is important in order to confirm the effects of WPS. Whilst tensile RS provide a benefit, this cannot be shown stochastically in C(T)s. Abstract: Warm pre-stressing (WPS) is the process of subjecting a pre-cracked component to a load cycle at a temperature higher than subsequent operating temperatures. This process is widely acknowledged as being able to enhance the load to fracture, especially in ferritic steels which exhibit lower shelf cleavage fracture. A WPS model developed by Chell and co-workers is reformulated to create a method of undertaking Monte Carlo Simulations to study the effects of WPS on brittle fracture. This requires the development of solution domains that are governed by the relative sizes of plastic zones ahead of the crack tip during the load and temperature cycles. Using recent experimental data it is shown that accurate estimates of the toughness distributions, after WPS, can be obtained. The scatter observed in this data is also replicated using these simulations. However, the accuracy of WPS predictions may be limited by the sample size. This analysis shows that a sample size smaller than 7 reduces the reliability of the results significantly. The enhancement caused by WPS can also be influenced by the presence of an existing residual stress field. It is shown that tensile residual stresses enhance the WPS effect (caused by an increase in both the pre-load magnitude and the unloaded state load level), provided that they do not cause premature fracture during the pre-load phase.